Metafora dalam Lirik Lagu Jepang yang Bertemakan Masa Depan: Kajian Semantik - Indamatul Mustaqimah, Siti Heriani; Trahutami, Sriwahyu Istana (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2025)
This research aims to determine the types of metaphors and the meanings in Japanese songs with the theme "Future". This research is a descriptive qualitative research using the theories of Stephen Ullman and Knowless and Moon. The data collection method used the simak method catat technique and analyzed using agih method with Pilah Unsur Langsung technique. The results of the research are presented informally. The results of 11 songs used, 27 data were found consisting of 3 anthropomorphic metaphors, 2 animalistic metaphors, 22 abstracting metaphors, and 2 synaesthetic metaphors. From the data analysis, it was also found that 19 lyrics contain positive connotation meaning, 8 lyrics contain negative connotation meaning, and 2 lyrics contain neutral connotation meaning.